2017
DOI: 10.1016/j.radcr.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Wandering carotid arteries: Reciprocating change between normal and retropharyngeal positions on serial CT studies

Abstract: Positional change in the retropharyngeal carotid artery, a rare phenomenon over time, is even rarer in previous reports, and it is important to be aware of this before any neck surgical procedure. A woman in her 50s underwent an anterior maxillectomy for upper gingival cancer, without neck dissection. The patient had medical histories of diabetes mellitus and liver dysfunction, with unremarkable family histories. Serial neck contrast-enhanced computed tomography for detecting locoregional recurrence had been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
(22 reference statements)
1
10
0
Order By: Relevance
“…Nonetheless, the definitive cause of this phenomenon remains unconfirmed. In the eight cases reported so far, positional change was confirmed at the level from the hyoid bone to the suprahyoid bone [1] , [2] , [3] , [4] , [5] , which is consistent with our case. It has been previously suggested that the position of the hyoid bone may be related to changes in the position of the carotid artery [1] .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Nonetheless, the definitive cause of this phenomenon remains unconfirmed. In the eight cases reported so far, positional change was confirmed at the level from the hyoid bone to the suprahyoid bone [1] , [2] , [3] , [4] , [5] , which is consistent with our case. It has been previously suggested that the position of the hyoid bone may be related to changes in the position of the carotid artery [1] .…”
Section: Discussionsupporting
confidence: 92%
“…Wandering carotid artery is a rare condition in which reciprocal positional changes of carotid artery is observed on serial contrast-enhanced CT examinations, with only three previous cases including this case [ 4 , 5 ]. In our case, the right common carotid artery moved between medial and lateral (normal) position on three MR studies, and was considered as a wandering carotid artery.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations